Why is your brand crisis? : challenging the representation of masculinity in the work of Richard Yates, Richard Ford, and Jonathan Franzen - Daly, Jennifer (Trinity College (Dublin, Ireland). School of English, 2016)
Through an analysis of American fiction, with a special focus on the writing of Richard Yates, Richard Ford, and Jonathan Franzen, this thesis argues that American men have always struggled with what it means to be an American Man, but that this does not equate to a crisis in masculinity. This thesis maintains that American culture propagates a myth of white masculinity in crisis more out of habit than any basis in fact, thereby ignoring how the American creed of achievement and success impacts on men and women alike. The Introduction lays out the theoretical framework which will be employed throughout this thesis. It discusses the theory behind the crisis in American masculinity, and engages with a number of prominent critics, such as Michael Kimmel and Sally Robinson, who endorse the concept of a gender-based crisis. This chapter situates the crisis theory in relation to aspects of American history such as the influence of the earliest settlers, and the conflict inherent in the establishment of the United States. It also analyses the concept of a masculinity crisis in relation to specific American social ideas such as the American dream, and exceptionalism.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin